2017
DOI: 10.1016/j.drugalcdep.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Energy drink use frequency among an international sample of people who use drugs: Associations with other substance use and well-being

Abstract: Highlights 74,864 people who use drugs participated in the online Global Drug Survey 2014  Energy drink, caffeine tablet and spray use was reported by 69.2%, 24.5% and 4.9%  Greater energy drink use frequency was associated with drug use  Greater use frequency was associated with hazardous drinking and poorer wellbeing 2 AbstractObjective: The study aims were to identify: i.) energy drink (ED), caffeine tablet, and caffeine intranasal spray use amongst a sample who report drug use, and ii.) the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Toxic and inflammatory effects of MDMA are exacerbated by its co-administration with other psychoactive substances (Khairnar et al 2010 , 2014 ). Caffeine is commonly consumed with MDMA in energy drinks to reduce drowsiness and fatigue, or it is present in illicit drug preparations, e.g., in ecstasy pills (Peacock et al 2017 ). Molecular mechanism of caffeine action in the brain is based on adenosine receptor antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic and inflammatory effects of MDMA are exacerbated by its co-administration with other psychoactive substances (Khairnar et al 2010 , 2014 ). Caffeine is commonly consumed with MDMA in energy drinks to reduce drowsiness and fatigue, or it is present in illicit drug preparations, e.g., in ecstasy pills (Peacock et al 2017 ). Molecular mechanism of caffeine action in the brain is based on adenosine receptor antagonism.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, the remaining sociodemographic and alcohol use differences between AmED and alcohol-only consumers were largely consistent between the online and street surveys and confirm what is reflected in international research -AmED consumers are younger, more likely to be male, more likely to have only secondary school education but also be currently studying, consume more alcohol in general, and report greater use of tobacco and other drugs. 10,[17][18][19][20][21][22] Although AmED users generally consume more alcohol than alcohol-only consumers, the role AmED plays in driving risky consumption remains unclear. 17,23 It may be that AmED consumers are attracted to EDs because they are prone to riskier consumption practices and risktaking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…One representative population study (n = 2000) in 2013 reported that only 5% of Australian adults had consumed AmED in the past 3 months; a higher rate of use (20%) was observed among people aged 18-24. 10 The other two studies targeted the younger ED consumer demographic: 42% of a community sample (n = 403) aged [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] reported AmED use in the past 6 months in 2011 11 , and 21% of adults interviewed in five Australian city entertainment precincts on weekend nights (n = 4227) reported AmED use in the past 12 hours in 2011-2012. 12 The lack of prevalence data and inconsistency in estimates across study designs points to the need to replicate these approaches to obtain further estimates of use.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol (ethyl alcohol; ethanol) and caffeine are the two most widely used psychoactive substances in the world (Ferreira & Willoughby, 2008; Cappelletti et al, 2015; Peacock et al, 2017). Episodic, moderate-to-heavy alcohol intake, such as during “binging,” constitutes the primary form of excessive alcohol consumption in the US.…”
Section: Introductionmentioning
confidence: 99%